The creativity of God world, Eucharist, reason - Davies, Oliver 1956- (Cambridge University Press, 2004)
We have, as a theological community, generally lost a language in which to speak of the created-ness of the world. As a consequence, our discourses of reason cannot bridge the way we know God and the way we know the world. Therefore, argues Oliver Davies, a primary task of contemporary theology is the regeneration of a Christian account of the world as sacramental, leading to the formation of a Christian conception of reason and a new Christocentric understanding of the real. Both the Johannine tradition of creation through the Word and a Eucharistic semiotics of Christ as the embodied, sacrificial and creative speech of God serve the project of a repairal of Christian cosmology. The world itself is viewed as a creative text authored by God, of which we as interpreters are an integral part. This is a wide-ranging and convincing book that makes an important contribution to modern theology
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Philosophical theology; Creation; Lord's Supper; Reason; Eucharistie; Kosmologie